A Case Study of TNB Network Solution & Support (NSS) Inventory Information System: A Quick Printable and Non-redundancy Web-based Application - Kian Lam Tan; ChenKim Lim (International Journal of Supply Chain Management, 2019)
This system is proposed to develop a web-based inventory information system for Network Solution & Support (NSS) department of Tenaga Nasional Berhad (TNB), Perak. The purpose of this study is to replace the conventional method which is the manual file system for managing inventory to online system where it can help to save the time especially in the process of updating the new inventory information. Besides that, the conventional method also contains the risk of duplicated files and leads to data redundancy and cost the memory wastage. NSS Inventory Information System is an alternative way to replace the manual file system so that multiple users can access the same data simultaneously at different stations. In addition, NSS Inventory Information System is based on Rapid Application Development (RAD) as the methodology where it involves the process of Requirement Planning, User Design, Construction and Cutover. Furthermore, it is developed by using Java programming language based on Vaadin Framework and MySQL as a database. Based on the testing and usability study, the result is very satisfying based on the staffs from NSS department and the contribution is able to help NSS department from TNB to update the inventory list by replacing the manual file system to a proper information system.